Is vitamin D status relevant to psoriasis and psoriatic arthritis? A retrospective cross-sectional study - Shirley Braga Lima Gamonal; Aloisio Carlos Couri Gamonal; Nathália Couri Vieira Marques; Marcos Antônio Fernandes Brandão; Nádia Rezende Barbosa Raposo (São Paulo Medical Journal, 2022)
Abstract BACKGROUND: Psoriasis is a systemic, immune-mediated disease characterized by inflammatory manifestations in the skin and joints. Vitamin D deficiency is currently considered a pandemic and is associated with comorbidities including psoriasis and psoriatic arthritis (PsA). OBJECTIVES: To determine the prevalence of hypovitaminosis D [25(OH)D] in patients with plaque psoriasis, with and without PsA, and of independent predictors of serum 25(OH)D levels. DESIGN AND SETTING: Retrospective cross-sectional study conducted among 300 patients at an outpatient clinic in a university center in Juiz de Fora, Minas Gerais, Brazil. METHODS: Demographic and clinical data (psoriasis area and severity index [PASI], family history, age at onset, disease duration, and the presence of PsA according to Classification Criteria for Psoriatic Arthritis), skin phototype, and season of the year were reviewed. RESULTS: Hypovitaminosis D (< 30 ng/mL) was highly prevalent in patients with psoriasis with and without PsA (82.2% and 74.9%, respectively). An inverse correlation between PASI and vitamin D was found (without PsA r = –0.59 and, PsA r = –0.52, P < 0.001), and multivariate regression revealed that hypovitaminosis D was associated with disease severity, season, and phototype. It was confirmed by binary logistic regression between PASI and vitamin D deficiency (< 30 ng/mL), (odds ratio, OR 1.78 CI: –0.20–0.53, P < 0.001). CONCLUSION: Hypovitaminosis D (< 30 ng/mL) was highly prevalent in psoriatic patients with and without PsA. Season and skin phototype were associated with 25(OH)D levels. An inverse association between PASI and serum 25(OH)D levels was established.